The influence of the 2010 World Cup mega-event on the image of the host country, based on the coverage by the Zero Hora newspaper - Remus, Renata Amaral; Pereira, Ana Cristina Cypriano (Organicom, 2011)
The understanding that a mega-event can influence the country that hosts it in different aspects, including its image, is the central focus of this research. Thus, South Africa, the host country of the mega sports event of the 2010 World Cup, was chosen as the object of study. For this purpose, the methodology for this research was an images audit in the media, when they were selected from among the main categories of inserts on South Africa, and analyzed in the Official World Cup insert of the Zero Hora newspaper, of Porto Alegre (RS). Finally, one understands that the considerations and results presented in this study may be valuable for the activity of public relations professionals, specially considering the proximity of holding the World Cup in Brazil.